Optimalisasi Media Sosial sebagai Strategi WOM Marketing: Studi Kasus pada Bengkel FST X Garage - Zulfaqqar Fadhil Atha Lathif; Muh. Najih Farihanto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the optimization of social media as a Word of Mouth (WOM) marketing strategy to enhance reputation and customer loyalty at FST X Garage, a modern automotive workshop in Magetan, Indonesia. The research is motivated by the growing competition in the automotive service industry and the increasing reliance of consumers on digital recommendations. Using a qualitative approach, data were collected through in-depth interviews, participatory observation, and social media content documentation. The analysis applied Miles and Huberman’s interactive model to identify WOM elements based on Jonah Berger’s Contagious theory, including Social Currency, Triggers, Emotion, Public, Practical Value, and Stories. The findings reveal that WOM at FST X Garage emerges organically through positive customer experiences, service transparency, and direct owner-customer interactions. Social media acts as a catalyst that amplifies public exposure through authentic User-Generated Content. The study implies that integrating service quality and digital communication is essential for building long-term reputation and provides practical insights for automotive service entrepreneurs in applying social media–based WOM strategies effectively.